2018
DOI: 10.53841/bpspag.2019.1.109-5.129
|View full text |Cite
|
Sign up to set email alerts
|

Self-care and social support in postgraduate study

Abstract: Postgraduate study can often be a challenging and lonely experience. We share our experiences and advice in managing looking after yourself during your research and study, giving particular focus to social support strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Based on this, it is concluded that with increasing social support, health‐promotion behaviors in the elderly also increase. This finding is in line with the studies of Stacey et al, Reef et al, and Stapley et al 25–27 In fact, social support facilitates healthy behaviors. Elderly people with adequate social support are more successful in following the recommended diet and medication.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on this, it is concluded that with increasing social support, health‐promotion behaviors in the elderly also increase. This finding is in line with the studies of Stacey et al, Reef et al, and Stapley et al 25–27 In fact, social support facilitates healthy behaviors. Elderly people with adequate social support are more successful in following the recommended diet and medication.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, socially isolated elderly may find it difficult to change their behavioral patterns, which makes them vulnerable. 25 Regarding the direct effect of attitude toward death on health-promotion behaviors in the elderly, the results showed that the path coefficients related to the relationship between fear of death and death avoidance with health-promotion behaviors were negative and the relationship between approach acceptance and health-promotion behaviors was positive and meaningful.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The demanding nature of postgraduate studies coupled with the unfamiliarity of the postgraduate environment can contribute to feelings of social isolation. Stacey, Talbot and Coxon (2019) argue that social support is integral to creating a positive postgraduate experience and that it is vital for students to build a social network with peers, friends, colleagues and family to help combat feelings of stress and social isolation. Kosi (2020) explains that social support can be subjective or objective.…”
Section: Social Isolation and Social Support During Postgraduate Studiesmentioning
confidence: 99%